Preparing the Thin Films from Laser Dye Dopped with Polymer and Measuring Thickness - Al-Dulaimi, G. S. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin films were prepared from melting coumrin C 2 dye in solvent DMF with PMMA with the same solvent and concentrations(1*10-2 5*10-3, 1*10-3 )M ,Films were either left on Flat surface for24hours or dried in avacuum oven for five hours at a temperature of 80c.The relative intensity of both the absorption and fluorescece spectrum are found to be increased with the increase of thickness of these films and concentration .Also the thickness of these films was measured by Mickelsons interfearing method.Also quantum efficiency of these films were measured too